Analisis Persepsi Mahasiswa Terhadap Pembelajaran Praktikum Dengan Menggunakan Metode Hybrid Learning pada Program Studi Pendidikan Teknologi Informasi - Farman, Indra; Ismail; Putri, Septi Malinda (TEKNOS: Jurnal Pendidikan dan Teknologi, 2023)
Higher education is experiencing a significant transformation with the development of information technology. Since the Covid 19 situation hit the whole world, it has also had a direct impact on the learning process, so it is necessary to implement learning using the hybrid learning method. The COVID-19 pandemic has drastically changed the educational landscape around the world, forcing educational institutions to evaluate and adapt their learning methods. Physical restrictions, school closures, campus closures. This research uses a qualitative descriptive method. The research subjects were determined purposively and the data sources chosen were information technology study program students and the data analysis technique used was qualitative descriptive. The results of this research show a positive response from students but there are still many shortcomings and obstacles in implementing learning using the Hybrid Learning method. This research aims to conduct an in-depth analysis of how students respond to and understand the use of hybrid learning methods in the context of practical learning.